Inhibition of Gastric Tumor Cell Growth Using Seed-targeting LNA as Specific, Long-lasting MicroRNA Inhibitors - Cathy Staedel; Christine Varon; Phu Hung Nguyen; Brune Vialet; Lucie Chambonnier; Benoît Rousseau; Isabelle Soubeyran; Serge Evrard; Franck Couillaud; Fabien Darfeuille (Elsevier, 2015)
MicroRNAs regulate eukaryotic gene expression upon pairing onto target mRNAs. This targeting is influenced by the complementarity between the microRNA "seed" sequence at its 5' end and the seed-matching sequences in the mRNA. Here, we assess the efficiency and specificity of 8-mer locked nucleic acid (LNA)-modified oligonucleotides raised against the seeds of miR-372 and miR-373, two embryonic stem cell-specific microRNAs prominently expressed in the human gastric adenocarcinoma AGS cell line. Provided that the pairing is perfect over all the eight nucleotides of the seed and starts at nucleotide 2 or 1 at the microRNA 5' end, these short LNAs inhibit miR-372/373 functions and derepress their common target, the cell cycle regulator LATS2. They decrease cell proliferation in vitro upon either transfection at nanomolar concentrations or unassisted delivery at micromolar concentrations. Subcutaneously delivered LNAs reduce tumor growth of AGS xenografts in mice, upon formation of a stable, specific heteroduplex with the targeted miR-372 and -373 and LATS2 upregulation. Their therapeutic potential is confirmed in fast-growing, miR-372-positive, primary human gastric adenocarcinoma xenografts in mice. Thus, microRNA silencing by 8-mer seed-targeting LNAs appears a valuable approach for both loss-of-function studies aimed at elucidating microRNA functions and for microRNA-based therapeutic strategies.